2016
DOI: 10.1038/srep33541
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Effects of Nitrogen Addition on Soil Respiration in a Semiarid Grassland

Abstract: Nitrogen (N) deposition has been steadily increasing for decades, with consequences for soil respiration. However, we have a limited understanding of how soil respiration responds to N availability. Here, we investigated the soil respiration responses to low and high levels of N addition (0.4 mol N m−2 yr−1 vs 1.6 mol N m−2 yr−1) over a two-year period in a semiarid Leymus chinensis grassland in Inner Mongolia, China. Our results show that low-level N addition increased soil respiration, plant belowground biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 43 publications
9
31
0
3
Order By: Relevance
“…Similarly, net ecosystem CO 2 exchange (NEE) and its components of gross ecosystem production (GEP) and ecosystem respiration (ER) may also respond nonlinearly to increasing N loading rates (Fleischer et al, 2013;Gomez-Casanovas et al, 2016;Tian et al, 2016). In the N-limited stage, low rates of N addition could stimulate ecosystem productivity (Aber et al, 1989), GEP (Fleischer et al, 2013;Gomez-Casanovas et al, 2016), and ER (Hasselquist et al, 2012;Zhu et al, 2016), while in the N saturation stage, high doses of N addition could have negative effects on GEP and ER (Treseder, 2008;Janssens et al, 2010;Maaroufi et al, 2015). The unbalanced responses of GEP and ER may lead to changes in NEE.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, net ecosystem CO 2 exchange (NEE) and its components of gross ecosystem production (GEP) and ecosystem respiration (ER) may also respond nonlinearly to increasing N loading rates (Fleischer et al, 2013;Gomez-Casanovas et al, 2016;Tian et al, 2016). In the N-limited stage, low rates of N addition could stimulate ecosystem productivity (Aber et al, 1989), GEP (Fleischer et al, 2013;Gomez-Casanovas et al, 2016), and ER (Hasselquist et al, 2012;Zhu et al, 2016), while in the N saturation stage, high doses of N addition could have negative effects on GEP and ER (Treseder, 2008;Janssens et al, 2010;Maaroufi et al, 2015). The unbalanced responses of GEP and ER may lead to changes in NEE.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown that the effects of N fertilizer application on CO 2 , CH 4 , and N 2 O emission are dependent on the form of N (Cai et al 2007;Peng et al 2011). Differences in soil structure and climate conditions between study sites may also have an effect, with the range of responses varying from no effect at all to positive or negative effects depending on ecosystem type, age, dominant plant species and soil chemical characteristics (Pregitzer et al 2008;Rodriguez et al 2014;Xiao 2017;Zhu et al 2016a), N loads in the soil in combination with climatic conditions (Alster et al 2013), and experiment duration (Zhou et al 2014). Grazing exclusion significantly decreased annual average CO 2 emission (Table 2) in our study.…”
Section: Ghg Fluxesmentioning
confidence: 98%
“…Soil moisture is an important determinant for altering soil respiration, especially under climate warming [146] . N addition either increased or decreased soil respiration, and such effects strongly depend on N level [147] .…”
Section: Responses Of Nutrient Cyclingmentioning
confidence: 98%